Meiotic behaviour of individual chromosomes of Festuca pratensis in tetraploid Lolium multiflorum - Kopecký, D; Lukaszewski, A J; Dolezel, J (Chromosome research, 2008)
Intergeneric hybrids of fescues (Festuca spp.) and ryegrasses (Lolium spp.) are unique for the ability of their chromosomes to pair essentially freely in meiotic metaphase I (MI). At the same time, their chromosomes can be readily recognized by genomic in-situ hybridization (GISH). Past genome-wide observations suggested that this homoeologous pairing was not completely random. In this study we extend the analysis to all seven individual chromosomes of F. pratensis introgressed into autotetraploid L. multiflorum and show that for any F. pratensis chromosome the choice of an MI pairing partner depends on the identity of the remaining chromosomes present in the quadruplet. In monosomic introgressions, the choice of a homologous or homoeologous partner was completely random; in disomics there was a slight preference for homologous pairing. Pairing preference was similar for each chromosome, suggesting that pairing affinity of all chromosomes is essentially the same and no structural rearrangements differentiate the two genera. Homoeologous crossover rates for individual chromosomes were similar and they were consistently lower than expected on the basis of the MI pairing. High homoeologous MI pairing in these hybrids may be due to a very permissive system of chromosome pairing control that overlooks differences between the parental chromosomes. Given the ease of genome discrimination by GISH in the Lolium-Festuca hybrids, the differences in repetitive DNA sequences must be substantial. On the other hand, it appears just as likely that while the DNA repeats diverged markedly during evolution, the sequences involved in chromosome pairing have been conserved enough to facilitate regular pairing partner recognition and crossing-over.
Keywords: rekombinace genetická; Hybridization, Genetic; Chromosomes, Plant; Metaphase; In Situ Hybridization; Recombination, Genetic; In Situ Hybridization, Fluorescence; hybridizace in situ; Festuca; Chromosome Pairing; Meiosis; hybridizace genetická; Genome, Plant; Lolium; párování chromozomů; metafáze; meióza; hybridizace in situ fluorescenční; jílek; chromozomy rostlin; polyploidie; Polyploidy; genom rostlinný